2002
DOI: 10.1034/j.1600-6143.2002.20607.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Unresectable Hepatoblastoma with Liver Transplantation in the Pediatric Population

Abstract: The purpose of our study was to evaluate the outcome of children who underwent liver transplantation as treatment for unresectable hepatoblastoma. We prospectively collected data on 311 consecutive liver transplants performed at Children's Medical Center of Dallas between October 1984 and November 2000. There were nine recipients (five boys, four girls) with a diagnosis of unresectable hepatoblastoma. Postoperative survival of those currently alive ranged from 6 months to 16 years (mean 6.4 years, median 7.7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…The actual 1-and 5-year survival rates are 78.6% and 65.5%, respectively, which are comparable with survival rates following both radical resection and deceased liver transplantation (6,9,(15)(16)(17)(18). Four children (28.6%) died from tumor recurrence after LDLT.…”
Section: Discussionsupporting
confidence: 56%
“…The actual 1-and 5-year survival rates are 78.6% and 65.5%, respectively, which are comparable with survival rates following both radical resection and deceased liver transplantation (6,9,(15)(16)(17)(18). Four children (28.6%) died from tumor recurrence after LDLT.…”
Section: Discussionsupporting
confidence: 56%
“…Because patients who receive CFV may develop secondary malignancies, and because immunosuppressive therapies necessary to control graft rejection after OLT lower the threshold for lymphoproliferative disorders, then sound rationale exists to limit chemotherapy exposure to patients who are deemed persistently unresectable when the decay plateau has been reached. However, despite encouraging results accumulating for OLT in the surgical algorithm for hepatoblastoma, our data regarding margin status continue to support aggressive partial hepatectomy, given limited organ resources and the need for life-long immunosuppression (18, 19). …”
Section: Discussionmentioning
confidence: 86%
“…Other single-center studies have reported similar success of OLT for unresectable HB [10][11][12]14]. In 2002, Pimpalwar and colleagues [14] showed 100% survival in patients who were chemoresponders and subsequently underwent OLT.…”
Section: Discussionmentioning
confidence: 88%
“…Despite this progress, disease-free survival for both HB and HCC is dependent upon resectability and complete surgical resection is essential for cure [5,6]. For patients with unresectable disease limited to the liver after chemotherapy, total hepatectomy and orthotopic liver transplantation (OLT) have become a recognized treatment option [7][8][9][10][11][12].…”
mentioning
confidence: 99%